Regulation of phosphatidylserine synthase from Saccharomyces cerevisiae by phospholipid precursors. - Poole, M A (1986)
The addition of ethanolamine or choline to inositol-containing growth medium of Saccharomyces cerevisiae wild-type cells resulted in a reduction of membrane-associated phosphatidylserine synthase (CDPdiacylglycerol:L-serine O-phosphatidyltransferase, EC 2.7.8.8) activity in cell extracts. The reduction of activity did not occur when inositol was absent from the growth medium. Under the growth conditions where a reduction of enzyme activity occurred, there was a corresponding qualitative reduction of enzyme subunit as determined by immunoblotting with antiserum raised against purified phosphatidylserine synthase. Water-soluble phospholipid precursors did not effect purified phosphatidylserine synthase activity. Phosphatidylserine synthase (activity and enzyme subunit) was not regulated by the availability of water-soluble phospholipid precursors in S. cerevisiae VAL2C(YEp CHO1) and the opi1 mutant. VAL2C(YEp CHO1) is a plasmid-bearing strain that over produces phosphatidylserine synthase activity, and the opi1 mutant is an inositol biosynthesis regulatory mutant. The results of this study suggest that the regulation of phosphatidylserine synthase by the availability of phospholipid precursors occurs at the level of enzyme formation and not at the enzyme activity level. Furthermore, the regulation of phosphatidylserine synthase is coupled to inositol synthesis.